Piper agroforestry in the Indian Himalayas: indigenous peoples’ practices, policies and incentives - Demsai Reang; Animekh Hazarika; Gudeta Weldesemayat Sileshi; Arun Jyoti Nath; Venkatesh Paramesh; W. Reshmi Singha; Ashesh Kumar Das (CABI Agriculture and Bioscience)
Abstract Background Indigenous populations across the world play a significant role in sustainable land management and conservation of biodiversity. However, indigenous agricultural practices are rarely studied in depth and remain poorly documented in many regions of the world. Documenting such practices and identifying policies and incentives that affect them can unlock their potential for better land management and biodiversity conservation. Methods We undertook household surveys and focus group discussions to document indigenous practices and the values of trees in Piper (Piper betle) agroforestry practiced by the ethnic Khasi (Pnar) community in the Indian Eastern Himalayas. We also undertook an in-depth vegetation sampling to quantify variations in phytosociology and tree diversity with stand age in Piper agroforestry and nearby native forests. In addition, we undertook strengths, weaknesses, opportunities and threats (SWOT) analysis and a desk review to identify policies, market support structures and incentives affecting cultivation of Piper, a cash crop of global importance. Results Unlike in shifting cultivation, indigenous people do not fell trees in the Piper agroforestry; instead, they allow trees to regenerate naturally and also enrich by planting tree seedlings in the gaps. Depending on the stand age, 30–49 tree species were recorded in the Piper agroforestry compared to 39 in nearby natural forests. While tree density was higher in the natural forests, greater species richness, diversity and basal area was recorded in > 25 years old Piper agroforestry stands. However, landholders do not have legally transferable or heritable rights to the land or trees. Conclusion It is concluded that the Piper agroforestry provides a pathway for averting land degradation due to shifting cultivation, biodiversity conservation and improving livelihoods of the indigenous community. Although existing policies are supportive, Piper agroforestry is not currently benefiting from incentives and market support structures. We recommend implementation of policies, market support structures, incentives and payment for ecosystem services so that indigenous communities can benefit from the global ecosystem services they provide.